Phosphorus-based intumescent coatings - Benítez, Juan C. (1998)
Fire is an energetic manifestation which carnes undesirable consequences due to the problems that it originates. The conflagration is a disagreeable fací produced by fire. The main objective of a fireproofing treatment is to make a material hardly flammáble or autoextinguishable. An ejficient fireproofing effect interrupts the combustión in one or more stadiums, leading the process to end in a reasonable period (preferably before ignition occurs). Intumescent coatings, as a means of passive protection against firet perform a fundamental role in this matter. Dry films of these paints, submitted to fíame action, softens in a first stage and then swells due to an intemal and partial loosing of non combustible gases, reaching up to 200 times of its original thickness. The charred coat, an incombustible spongy mass, protects the painted material’ delays the temperature increase and avoids the access of air, and so the combustión. By means of intumescent coatings, different materials such as paper, wood, pasteboard, plastics, metáis, etc. can be protected The objective of this paper was to study the influence of some formulation variables of phosphorus-based intumescent coatings, formulated and manufactured for this experiment. Chlorinated rubber coatings based on ammonium polyphosphate, pentaerythritol, melamine, 42 % chlorinatedparaffin and an endothermic filler showed very high performance after ageing.